2020
DOI: 10.1080/22221751.2020.1773325
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the gonococcal FC428 penA allele 60.001 on ceftriaxone resistance and biological fitness

Abstract: Global dissemination of the Neisseria gonorrhoeae ceftriaxone-resistant FC428 clone jeopardizes the currently recommended ceftriaxone-based first-line therapies. Ceftriaxone resistance in the FC428 clone has been associated with the presence of its mosaic penA allele 60.001. Here we investigated the contribution penA allele 60.001 to ceftriaxone resistance and its impact on biological fitness. Gonococcal isolates expressing penA allele 60.001 and mosaic penA allele 10.001, which is widespread in the Asia-Pacif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 49 publications
0
25
0
Order By: Relevance
“…Furthermore, the high-level ceftriaxoneresistant F89 isolate, which emerged in this genomic background, was reported only in France and Spain [14] and its spread was likely limited by a decreased biofitness [18]. The ceftriaxone-resistant F90 and F91 isolates, associated with the internationally spreading FC428 clone containing penA-60 [5,[7][8][9][10][11][12], appeared in France in 2017 and 2019, respectively [5,7]. Notably, the patient with F91 was infected by her husband, who acquired the infection from a sex worker in Cambodia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the high-level ceftriaxoneresistant F89 isolate, which emerged in this genomic background, was reported only in France and Spain [14] and its spread was likely limited by a decreased biofitness [18]. The ceftriaxone-resistant F90 and F91 isolates, associated with the internationally spreading FC428 clone containing penA-60 [5,[7][8][9][10][11][12], appeared in France in 2017 and 2019, respectively [5,7]. Notably, the patient with F91 was infected by her husband, who acquired the infection from a sex worker in Cambodia.…”
Section: Discussionmentioning
confidence: 99%
“…Resistance to ESCs was conferred by the novel mosaic penA allele designated as penA-237.001, encoding an amino acid sequence 99.1% identical (i.e. five substitutions: P328A, A480P, S483T, I485T and T534A; nucleotide identity: 98.7%) to that encoded by penA-60.001, which causes ESC resistance in the internationally spreading FC428 clone [5,[7][8][9][10][11][12]. The penA-237.001 encodes a mosaic penicillin-binding protein 2 (PBP2) including the amino acid substitutions A311V, I312M, V316T and G545S associated with ESC resistance [13].…”
Section: Molecular Investigationmentioning
confidence: 99%
See 1 more Smart Citation
“…These results illustrated that the emergence of dual-resistant FC428-related strains in Guangdong Province is the result of multiregional population exchanges. Meanwhile, FC428 has increased fitness ( 19 ); thus, the spread of dual-resistant FC428-related clones might have a huge impact on ceftriaxone and azithromycin efficacy. Overall, we should track the prevalence of dual-resistant clones in future surveillance to effectively curb the large-scale spread of dangerous strains.…”
Section: Discussionmentioning
confidence: 99%
“…A Chinese study revealed an increase of the ceftriaxone-decreased-susceptibility from 2.05% (2016) to 16.18% (2019) [ 85 ]. Therefore, this global rapid ascension of the FC428 N. gonorrhoeae jeopardizes the current treatment guidelines and may announce a hereafter global AMR to ceftriaxone and cefixime in gonorrhea patients [ 86 ].…”
Section: Treatment Guidelines and Resistant Pathogensmentioning
confidence: 99%